2013
DOI: 10.1089/chi.2013.0069
|View full text |Cite
|
Sign up to set email alerts
|

Parents and Pediatric Weight Management Attrition: Experiences and Recommendations

Abstract: Parental responses appeared to express frustration about flexibility with appointment times and treatment locations. The most frequently desired components were those traditionally offered by stage 3 pediatric weight management programs/clinics, and this may suggest a need for treatment delivery of these components to be more individualized. Additional discussion with families about their desire to discontinue treatment may provide a timely opportunity to address this need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Moreover, most families indicated that a comprehensive assessment and plan for tailored care based on the home environment would allow clinicians to better meet the needs and priorities of families, by assisting clinicians in providing practical recommendations and support. Viewing families’ social and physical environments first‐hand and tailoring care based on specific needs may help to enhance retention and engagement, increase rapport between families and clinicians and optimise outcomes . It is notable that although most of the families that we interviewed indicated their willingness to participate in home visits, the main reason that families declined to participate in our study was due to lack of time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most families indicated that a comprehensive assessment and plan for tailored care based on the home environment would allow clinicians to better meet the needs and priorities of families, by assisting clinicians in providing practical recommendations and support. Viewing families’ social and physical environments first‐hand and tailoring care based on specific needs may help to enhance retention and engagement, increase rapport between families and clinicians and optimise outcomes . It is notable that although most of the families that we interviewed indicated their willingness to participate in home visits, the main reason that families declined to participate in our study was due to lack of time.…”
Section: Discussionmentioning
confidence: 99%
“…Since family caregivers play a prominent role in these well‐established treatments, seeking the input of caregivers is critical for the effective delivery of behavioural treatment . While most studies have captured caregiver perspectives at treatment initiation , completion or treatment withdrawal , with feedback specific to intervention approaches , barriers to treatment and reasons for attrition , few studies have captured caregiver experiences related to the psychological and social ramifications of having an obese child .…”
Section: Introductionmentioning
confidence: 99%
“…18 Clinic staff should seek to understand families' expectations for treatment so that treatment elements can be tailored as much as possible to maximize retention. 19 Novel methods of providing treatment, such as telehealth, also may help reduce barriers to clinic attendance. 20 Research should be conducted to characterize patients who are successful after just 2 visits vs 3 or more visits, which could help maximize scarce treatment resources.…”
Section: Discussionmentioning
confidence: 99%